Undergraduates’ Perceptions of Job Interview Assessment for Career Readiness of a University English Language Course - Nurzarina Abdul Samad; Hazila Kadir @ Shahar (Development in Language Studies, 2024)
This study focuses on the career readiness among the final year undergraduates through job interview assessment in an English language course. Issues related to the lack of preparation, language incompetency and poor self-confidence are some factors of unemployment among Malaysian graduates. Therefore, this study was conducted to explore the aspects that the participants could improve as reflected by themselves and other components that could be integrated into the course for future reference. This study was conducted by distributing an open-ended survey to 80 participants comprising local and foreign. The analysis highlighted three aspects including the significance of job interview assessment for career readiness, self-reflection from the participants on their job interview assessment and other components that can be included in the course in the future. The findings show that the participants find the job interview to be very helpful for their career readiness. Furthermore, they would like to improve themselves in terms of their fluency, self-confidence, answering skills, and body language. The implication of this study is for the higher institutions to be more aware about the importance of having mock job interviews as part of the undergraduates’ preparation for their future career.